The relationship between network ranking and research performance: an application to the Italian national council of research. (2016) - Falavigna, Greta; Manello, Alessandro
Considering the Italian National Research Council (CNR), this study aims at analysing whether relationships between researchers from different scientific institutions affect the quality of scientific outputs. On the one hand, authors applied a directional output distance function (DODF) to measure internal performances of research institutes. Authors consider two different kinds of scientific outputs, assuming some outputs more important than others, as well as established by the last CNR reform. On the other hand, in order to evaluate collaborations among CNR institutes, as well as between CNR institutes and universities, a network analysis has been applied with the aim of measuring relationships among researchers. In this case, research institutes are seen as nodes of the internal collaboration network. In this paper, authors used data of scientific publications related to all institutes of CNR for the 2007 year and they asked to the question whether best researchers in terms of publications are those that collaborate more.